Investigating Maturity State and Internal Properties of Fruits Using Non-destructive Techniques-a Review - Mohd Fadzli Abd Shaib; Ruzairi Abdul Rahim; S. Z. M. Muji; Azian Abd Aziz Ahmad (Universitas Ahmad Dahlan, 2017)
The evaluation of internal condition of the fruit via destructive techniques mostly damaged the internal and external fruit structure. However, there are several non-destructive techniques available could be applied in the agricultural industry, specifically for observing internal fruit conditions. Different kinds of internal conditions of fruits are evaluated in terms of their quality and ripeness levels. These non-destructive techniques include fruit evaluation via ultrasonic measurement techniques, light spectroscopy, imaging via Magnetic Resonance Imaging (MRI) and X-Ray, computer vision, electric nose and also vibration. The capabilities and the effectiveness of these techniques towards fruit monitoring are thoroughly discussed. Besides, the drawback of these non-destructive technique has been analysed.